뉴스서비스별 전자투표시스템 관련 가짜뉴스가 뉴스 이용자의 이용 태도, 선거 참여 의도, 뉴스서비스 신뢰도에 미치는 영향 - 진소연(So-Yeon Jin); 이지은(Ji-Eun Lee) (한국콘텐츠학회 논문지, 21(1), 2021)
This study pays attention to the fact that the fake news is attracting attention because it causes various social problems. To find out these fake news' influence, the study conducted the experiment to examine that the fake news related to the electronic voting system affects on the news users' attitude of using the system, intention to participate in the election through the system and reliability of news services. The results have shown that the fake news framed with negative contents reduced users' attitude of using the system and intention of participation in the election. Especially, as a result of examining the difference in the fake news' influence according to each news services, in the case that users recognized that the news was fake after exposing to the general internet news, the attitude of using the system and the intention of participation in the election have reduced and recovered again. However, users who exposed to Naver, Facebook believed the negative content of the fake news more strongly. Through these results, this study empirically confirmed that the fake news has a tendency to exert influence on users' cognitive dimension and to reinforce awareness in a direction consistent with the initial exposure information. 본 연구의 목적은 가짜뉴스가 크고 작은 사회적 문제를 야기한다는 점에 주목하여, 전자투표시스템 관련 가짜뉴스가 뉴스 이용자의 시스템 이용에 대한 태도, 시스템을 통한 선거 참여 의도, 뉴스서비스 신뢰도에 어떠한 영향력을 미치는지 실험을 통해 확인하는데 있다. 연구결과, 부정적인 내용으로 프레임된 가짜뉴스는 이용자의 태도와 선거 참여 의도 수준을 감소시키는 효과를 보였다. 특히 각 뉴스서비스에 따른 가짜뉴스 영향력 차이를 검증한 결과, 이용자가 일반 인터넷신문을 통해 가짜뉴스에 노출되고 해당 뉴스가 가짜임을 인지한 경우에는 태도와 선거 참여 의도 수준이 감소 후 다시 회복되는 모습을 보였다. 하지만 네이버와 페이스북 가짜뉴스에 노출된 이용자들은 가짜뉴스에 담긴 부정적인 내용을 더욱 강하게 형성하는 것으로 나타났다. 가짜뉴스가 이용자의 인지적 차원에 영향력을 행사하고, 최초 노출 정보와 일치하는 방향으로 인식을 강화하려는 경향이 있다는 사실을 실증적으로 확인하였다.